Are Supernovae Responsible for the Gamma Ray Spectrum from the Galactic Center? - Todor Stanev (Acta Polytechnica CTU Proceedings)
We discuss the supernova remnants distribution as a function of the galactic longitude and compare their positions to that of the detected TeV gamma ray sources. A large fraction of these sources either coincide or a close by known supernova remnants. If we look within 10o of the Galactic center most identied sources are combinations of supernova remnants with giant molecular clouds. The diffuse gamma ray flux from the direction of the Galactic center is much smaller.